2014
DOI: 10.1016/j.jcrysgro.2013.12.033
|View full text |Cite
|
Sign up to set email alerts
|

On the use of methane as a carbon precursor in Chemical Vapor Deposition of silicon carbide

Abstract: Abstract:It is generally considered that methane is not a suitable carbon precursor for growth of silicon carbide (SiC) epitaxial layers by chemical vapor deposition (CVD) since its use renders epitaxial layers with very high surface roughness. In this work we demonstrate that in fact SiC epitaxial layers with high-quality morphology can be grown using methane. It is shown that a key factor in obtaining high-quality material is tuning the C/Si ratio of the process gas mixture to a region where the growth is li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Thus, the kinetics of the hydrocarbon chemistry was less well investigated. Moreover, experimental results performed by our group 132 , showed that there were difference in the growth rates and surface roughness when different hydrocarbons were used as precursors. This led us to study the gas-phase kinetics of hydrocarbons presented in the literature.…”
Section: Chapter 4 Results and Summarymentioning
confidence: 99%
“…Thus, the kinetics of the hydrocarbon chemistry was less well investigated. Moreover, experimental results performed by our group 132 , showed that there were difference in the growth rates and surface roughness when different hydrocarbons were used as precursors. This led us to study the gas-phase kinetics of hydrocarbons presented in the literature.…”
Section: Chapter 4 Results and Summarymentioning
confidence: 99%
“…A very high surface roughness is produced by the combination of SiH 4 +HCl and CH 4 , suggesting that these conditions are out of the narrow chemical window needed for deposition with this precursor combination. 7 The AFM images for the precursor combinations at C/Si = 0.6 are given in Figure 6. It can be seen that SiH 4 +HCl gives step bunched surfaces at this silicon rich condition, in line with previous findings.…”
Section: Resultsmentioning
confidence: 99%
“…Except for SiH 4 +HCl which gives very rough morphology with CH 4 at C/Si = 0.6, which is in line with our previous findings. 7 One could suggest that the lower surface roughness for SiCl 4 is due to a lower growth rate in the carbon limited chemistry. But while the growth rate indeed drops 29%, from around 105 μm/h at C/Si = 1 to 75 μm at C/Si = 0.6 when using SiCl 4 , the growth rate for SiHCl 3 drops 27%, from 110 to 80 μm/h for SiHCl 3 , and the growth rate for SiH 4 +HCl drops 37%, from 95 to 60 μm/h for SiH 4 +HCl.…”
Section: Resultsmentioning
confidence: 99%
“…This is opposite to when CH 4 is used in chlorinated SiC CVD, where good growth conditions are confined to a narrower C/Si ratio window than when using C 2 H 4 as the C precursor. 28 The different rates at which growth species are formed from the precursors also suggests that combining different amounts of different precursors could be a way of controlling the spatial profile of the growth species impingement rate, and thereby the spatial profile of the C/Si impingement ratio.…”
Section: Discussionmentioning
confidence: 99%